Who are you, Griselda? A replacement name for a new genus of the Asiatic short-tailed shrews (Mammalia, Eulipotyphla, Soricidae): molecular and morphological analyses with the discussion of tribal affinities - Anna A. Bannikova; Paulina D. Jenkins; Evgeniya N. Solovyeva; Svetlana V. Pavlova; Tatiana B. Demidova; Sergey A. Simanovsky; Boris I. Sheftel; Vladimir S. Lebedev; Yun Fang; Love Dalen; Alexei V. Abramov (ZooKeys, 2019)
The first genetic study of the holotype of the Gansu short-tailed shrew, Blarinella griselda Thomas, 1912, is presented. The mitochondrial analysis demonstrated that the type specimen of B. griselda is close to several recently collected specimens from southern Gansu, northern Sichuan and Shaanxi, which are highly distinct from the two species of Asiatic short-tailed shrews of southern Sichuan, Yunnan, and Vietnam, B. quadraticauda and B. wardi. Our analysis of four nuclear genes supported the placement of B. griselda as sister to B. quadraticauda / B. wardi, with the level of divergence between these two clades corresponding to that among genera of Soricinae. A new generic name, Parablarinella, is proposed for the Gansu short-tailed shrew. Karyotypes of Parablarinella griselda (2n = 49, NFa = 50) and B. quadraticauda (2n = 49, NFa = 62) from southern Gansu are described. The tribal affinities of Blarinellini and Blarinini are discussed.